Effect of asymptomatic vaginal colonization with Candida albicans on pregnancy outcome. (14th July 2015) - Farr, Alex; Kiss, Herbert; Holzer, Iris; Husslein, Peter; Hagmann, Michael; Petricevic, Ljubomir
Abstract Introduction Vaginal infection is a major causative factor of preterm delivery. The present study was performed to evaluate the effect of asymptomatic vaginal colonization with Candida albicans at early gestation on pregnancy outcome. Material and methods From 2005 to 2014, a total of 8447 women with singleton pregnancies between 10+0 and 16+0 gestational weeks were routinely subjected to an antenatal infection screen‐and‐treat program. Vaginal smears were Gram‐stained and microscopically evaluated, and data were retrospectively analyzed. Women exposed to Candida received clotrimazole and were re‐tested after 4–6 weeks. Treatment was repeated in case of recurrence. Women with normal or intermediate vaginal flora were considered as non‐exposed. Bacterial vaginosis and trichomoniasis were assessed and treated as well. Descriptive data analysis, chi‐squared testing and multiple regression analysis with adjustment for potential confounders were performed. Rates of asymptomatic vaginal infections, preterm delivery and low birthweight served as the main outcomes measures. Results A normal or intermediate flora was found in 6708 (79.4%) of the screened women; 1142 women (13.5%) showed asymptomatic C. albicans infection. Of this group, 185 women (2.2%) had a recurrence of Candida on vaginal smears. Compared with the non‐exposed women with normal or intermediate flora, those with recurrent candidiasis had higher rates of preterm delivery (11.9% vs. 9.5%) and of low birthweight (10.8% vs. 8.0%), as confirmed in the multiple model (p = 0.02). Conclusions Recurrent asymptomatic vaginal colonization with Candida in early pregnancy is associated with preterm delivery and low birthweight. Routine screening and consequent treatment for candidiasis could improve pregnancy outcomes.